Nutritional, Safety and Sensory Evaluation of Innovative Siwi Date Snacks with Flavors and Fillings - Neveen F. Agamy; Eman M. Hegazy; Nashwa M. Younes; Ayah M. El-Hossainy (Journal of High Institute of Public Health, 2023)
Background: Due to their nutritional benefits and economic importance, dates are essential for all ages, nations, and civilizations. Dates include some nutritional components that can boost their nutritious worth. Objective(s): We aimed to assess the quality and safety attributes of Siwi semi-dry dates and their products with diverse tastes and fillings by measuring their chemical composition, safety features, and sensory aspects. Methods: Eleven Siwi semi-dry date products were evaluated. The flavors were milk, coconut, Oreo, cinnamon, coffee, Nescafé, cappuccino, caramel, peanut butter, Lotus, and Nutella. Additionally, our study assessed their chemical composition, including vitamin and mineral content besides evaluating their quality, safety, and sensory characteristics. Statistical analysis was performed, with a 5% least significant difference calculated for each treatment. Results: This study investigated Siwi semi-dry date snacks, revealing distinct nutritional profiles. Dark mix whole dates had the highest calorie, protein, and fat content; while plain whole dates had the lowest. Plain whole dates were rich in carbohydrates and sugars. Dark mix whole dates generally showed elevated vitamin and mineral levels. Quality attributes like texture favoured plain whole dates. Microbiological analysis confirmed safety, with no aflatoxins detected. Sensory evaluation ranked milk whole dates as the highest for colour, taste, odour, texture, and overall acceptance. These insights provide comprehensive overview, valuable information for both consumers and producers of Siwi semi-dry date snacks. Conclusion: Our study confirmed that dates are a significant food source for carbohydrates, fibres, minerals, and vitamins.